A concise course on the theory of classical liquids : basics and selected topics - Santos, Andrés (Springer Berlin Heidelberg, 2018)
This short primer offers non-specialist readers a concise, yet comprehensive introduction to the field of classical fluids - providing both fundamental information and a number of selected topics to bridge the gap between the basics and ongoing research. In particular, hard-sphere systems represent a favorite playground in statistical mechanics, both in and out of equilibrium, as they represent the simplest models of many-body systems of interacting particles, and at higher temperature and densities they have proven to be very useful as reference systems for real fluids.